Ablation in different heat fluxes of C/C composites modified by ZrB2–ZrC and ZrB2–ZrC–SiC particles - Liu, Lei; Li, Hejun; Feng, Wei; Shi, Xiaohong; Li, Kezhi; Guo, Lingjun (Corrosion science, 2013)
•Two heat fluxes were used to evaluate the ablation of modified C/C composites.•C/C–ZrB2–ZrC–SiC has the lowest ablation rate under a heat flux of 2.38MW/m2.•Ablation rates of C/C shows the smallest increase with increase in heat flux.•Thermal mismatch and evaporation of SiO2 dominate variations in the ablation behavior. Carbon/carbon composites modified by ZrB2–ZrC–SiC particles (C/C–Z–SiC), C/C–Z and C/C were ablated by oxyacetylene torch using two different heat fluxes to investigate the effect of doped ceramic particles. Results indicated that C/C–Z–SiC had the best ablation property in heat flux of 2.38MW/m2 whereas their ablation rates increased fastest when heat flux rising from 2.38 to 4.18MW/m2. C/C composites had the poorest ablation property in the lower heat flux and their ablation rates increased slowest. Thermal mismatch of Z, SiC and C and evaporation of SiO2 induced the various ablation behavior.